Analisis Determinan Indeks Pembangunan Manusia Di Wilayah Subosukawonosraten Tahun 2006-2013 - Kasanah, Nurul (2016)
Human development is a process of development that aims to be able to have more choices, particularly in income, health and education. One criterion can be seen through the Human Development Index. The purpose of this study was to analyze how the effect of economic growth, poverty, unemployment, and shopping areas of the human development index. The analytical method used in this research using panel data regression analysis of the effects of random (Random Effect Method / REM). The results of this study indicate that economic growth is positive and significant effect on the Human Development Index (HDI), poverty and significant negative effect on the Human Development Index (HDI), the unemployed no significant effect on the Human Development Index (HDI), and shopping areas and significant positive effect on the Human Development Index (HDI) in the region SUBOSUKAWONOSRATEN. Keywords : Economic Growth, Poverty, Unemployment, Human Development Index